Bizzy Bear : fire rescue! - Davies, Benji; Nosy Crow Ltd. (Somerville, Mass. : Nosy Crow, 2013)
"Bizzy Bear the firefighter is coming to the rescue! Join the fun in this sturdy book with sliders and tabs to push and pull."--From the publisher.
Cover title.
new kids book 2025 fall.
Ages 1-3.
Keywords: Fire fighters -- Juvenile fiction; Bears -- Juvenile fiction; Fire fighters -- Fiction; Bears -- Fiction; Board books; Stories in rhyme; Toy and movable books -- Specimens